Cinta dan Tradisi: Akulturasi Budaya Dalam Pernikahan Antara Masyarakat Pendatang dan Lokal di Dusun Limbur Baru - Harpinsyah Harpinsyah; Mulia Jaya; M. Safiq (Universitas Muara Bungo, 2024)
This study aims to examine the process of cultural acculturation in the context of marriage traditions between Javanese migrants and the local community in Dusun Limbur Baru, Bungo Regency, Jambi. The research explores the cultural interactions that occur through the blending of marriage traditions from both cultural groups and their impact on the cultural identity of the local community. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The findings reveal that the cultural acculturation process in Dusun Limbur Baru resulted in a unique collaboration in the implementation of marriage traditions, where elements of migrant culture were integrated with local customs. Despite challenges such as differences in cultural values and economic constraints, the community successfully created new traditions that reflect cultural tolerance and harmony. Additionally, this acculturation has had a positive impact by enriching the local cultural identity, although attention is still needed to preserve the core elements of the original traditions. This study provides insights into how cultural collaboration can strengthen social relationships and create a dynamic shared identity in multicultural societies.